RISK MANAGEMENT IN PROJECT FINANCING OF FERRONICKEL PROJECT: A CASE STUDY OF PT NIKEL MAJU BERSAMA - Edward Veldman; Sylviana Maya Damayanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to identify key financial risks in the financing strategy of the Venus Project by PT Nikel Maju Bersama (PT NMB), and to develop effective mitigation plans to ensure the project's continuity and success. The Venus Project is part of Indonesia’s nickel down streaming agenda supporting the electric vehicle (EV) battery ecosystem. A qualitative approach was applied through in-depth interviews and Focus Group Discussions (FGDs) with internal and external stakeholders. Data analysis employed coding methods, SWOT, PESTEL, and stakeholder mapping. The findings reveal that financial risks such as funding delays, capital cost overruns, and market uncertainty significantly threaten project viability. Moreover, the lack of formal documentation on mitigation strategies was noted. Based on these findings, the study proposes a comprehensive risk management framework, including mitigation strategies such as optimized capital structure, financial hedging, and robust covenant design. This study contributes practical insights into financial risk management for large-scale mining projects, especially those utilizing project finance structures. Keywords: Risk Management, Project Financing, Ferronickel, Nickel Down streaming, PT Nikel Maju Bersama